Transpersonal Values Unveiled: A Study On Self-Regulated Learning Model - Yudhi Munadi; Abuddin Nata; E. Bahruddin; Maemunah Sa’diyah (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2022)
AbstractReviving transpersonal values in higher education through lectures lacks a proven effective model. Current learning is predominantly expository, focused on cognitive knowledge mastery in classrooms, neglecting experiential exploration and the full potential of peer interaction and environmental resources. A culture of value-based learning has yet to be established. This descriptive qualitative study aims to uncover transpersonal values within the Self-Regulated Learning (SRL) model applied to Media dan Teknologi Pembelajaran (MTP) courses. Data on transpersonal values are collected through interviews and open-ended questions, validated through member-checking using a Likert scale with 122 participants. The MLT's SRL model comprises six stages: task understanding, planning, preparation, exploration, assessment, and reflection. These stages reveal values such as intention, inclusivity, responsibility, spiritual intelligence, trustworthiness, patience, self-reflection, self-observation, and character refinement. Empowering individual autonomy, these steps guide actions towards acquiring information, expertise, self-improvement, and heightened spiritual awareness. Abstrak Menghidupkan kembali nilai-nilai transpersonal di perguruan tinggi melalui perkuliahan belum memiliki model yang terbukti efektif. Pembelajaran saat ini cenderung bersifat ekspositoris, berfokus pada penguasaan pengetahuan kognitif di dalam ruang kelas, yang mengabaikan eksplorasi pengalaman dan potensi penuh interaksi dengan teman sebaya dan sumber daya lingkungan. Budaya pembelajaran berbasis nilai-nilai juga belum terbentuk dengan baik. Studi deskriptif kualitatif ini bertujuan untuk mengungkap nilai-nilai transpersonal dalam model Self-Regulated Learning (SRL) yang diterapkan pada mata kuliah Media dan Teknologi Pembelajaran (MTP). Data mengenai nilai-nilai transpersonal dikumpulkan melalui wawancara dan pertanyaan terbuka, kemudian divalidasi melalui member-checking menggunakan skala Likert dengan 122 partisipan. Model SRL MLT terdiri dari enam tahapan: pemahaman tugas, perencanaan, persiapan, eksplorasi, penilaian, dan refleksi. Tahapan-tahapan ini mengungkapkan nilai-nilai seperti nilai intensi, inklusif, tanggung jawab, cerdas spiritual, amanah, sabar, muhasabah, muraqabah, dan tahsinul akhlaq Dengan memberdayakan otonomi individu, langkah-langkah ini memandu tindakan menuju perolehan informasi, keahlian, peningkatan diri, dan kesadaran spiritual yang lebih tinggi.How to Cite : Munadi, Y., Nata, A., Bahruddin, E, Sa’diya, M. (2022). Transpersonal Values Unveiled: A Study On Self-Regulated Learning Model. TARBIYA: Journal of Education in Muslim Society, 9(2), 211-226. doi:10.15408/tjems.v9i2.32827.